The Determinant of Sustainability Report Disclosure - Sari, Maylia Pramono; Sakinah, Nafiatus; Utaminingsih, Nanik Sri; Raharja, Surya (Universitas Negeri Semarang, 2023)
The aim of this study was to evaluate and confirm the influence of the determinant of Sustainability Report Disclosure with the audit committee meeting acting as a moderating variable. LQ45 firms that were listed on the Indonesia Stock Exchange (IDX) between 2017 and 2020 made up the study's sample (42 companies). Purposive sampling was the method of sampling that was employed in this investigation which included 113 analytical units to acquire data for this study. These methods included obtaining annual reports and sustainability reports for the LQ45 company from the IDX official website. This study's data analysis method included both moderating regression analysis (MRA) and panel data regression analysis with the chosen model being the Fixed Effect Model (FEM). The analysis of this study's data shows that leverage has a negative impact on the disclosure of sustainability reports, company size has no impact, and profitability has a positive impact on the disclosure of sustainability reports. The audit committee meeting can moderate (weaken) the relationship between profitability and sustainability report disclosure, but can it moderate the relationship between leverage and firm size on sustainability report disclosure.